Plan Quality Assessment of Fractionated Stereotactic Radiotherapy Treatment Plans in Patients With Brain Metastases - Simon, Mihály; Papp, Judit; Csiki, Emese; Kovács, Árpád (Frontiers in Oncology, 2022)
Background and Purpose The treatment options available in the management of brain metastases includes fractionated stereotactic radiotherapy (FSRT) and stereotactic radiosurgery (SRS) treatments. FSRT treatments have proved to be useful mainly in the treatment of larger volumes. This study aims to evaluate the FSRT treatment technique used in our department based on various plan quality indices. Methods and Materials 24 treatment plans of 23 patients were analyzed. Volumetric modulated arc therapy (VMAT) plans were generated in line with the department protocol. The following parameters were extracted: Radiation Therapy Oncology Group conformity index (RTOG CI), Paddick conformity index (Paddick CI), gradient index (GI), quality index (Q), homogeneity index (HI), and V24.4 volume as a parallel index of V12 used at SRS plan evaluation. Results Plan conformity was acceptable, RTOG CI mean was 0.942; Paddick CI mean was 0.824. The mean GI value was 6.146. The mean of HI and Q indices were 1.263 and 0.94, respectively. V24.4 mean was 33.434 cm3. All plans achieved clinically acceptable organs-at-risk (OAR) constraints. PTV volumes were clustered into either 10 cm3 or 15 cm3 bins depending on the plan quality metric we used. The mean values show a balanced distribution of plan indices along the various PTV bins. Discussion Our results based on the derived indices show that our FSRT approach can achieve clinically acceptable treatment plans. Furthermore, the clustering of PTV volumes show that these plan quality metrics remain acceptable for a wide spectrum of PTV volumes.